Nursing of recurrent malposition of peripherally inserted central catheters in a patient with thoracic outlet syndrome and related nursing measures (1例胸廓出口综合征患者经外周静脉置入中心静脉导管置管反复原发性异位的护理) - ZHANG Liuyan (张柳燕); HUANG Guohua (黄果花); LI Xiufeng (李秋凤) (中西医结合护理)
This paper summarized the potential causes and nursing measures of recurrent malposition of peripherally inserted central catheters (PICC) in a patient with thoracic outlet syndrome and related nursing measures. Thoracic outlet syndrome is a relatively rare peripheral neurovascular entrapment disease, also known as brachial plexus neurovascular compression in China, and there are very few clinical cases of primary malposition and difficulty in feeding indwelling PICC catheters in such patients. Through the case studies, it is believed that pre-catheterization history assessment, catheterization history, laboratory and imaging tests are the first priority, and post-ectopic management, complication prevention, psychological care, and health education are the key. This patient failed to pass the bedside catheter placement, and the Interventional Vascular Department was asked to mediate tube under the digital subtraction angiography (DSA). There were no complication such as thrombosis and infection after the catheter placement, and the patient successfully completed autologous stem cell transplantation and was discharged from the hospital. (本文总结1例胸廓出口综合征患者经外周静脉置入中心静脉导管(PICC)置管原发性异位的原因及护理经验。胸廓出口综合征是临床上比较少见的周围神经血管卡压性疾病, 又称为臂丛神经血管受压征, 此类患者留置PICC导管出现原发性异位及送管困难的临床病例报告极少。通过案例分析认为置管前的病史评估、置管史、实验室及影像学检查是首要, 异位后的处理、预防并发症、心理护理、健康教育是关键。此患者经床边调管失败, 请血管介入科在数字减影血管造影下成功调管, 调管后未出现血栓及感染等并发症, 顺利完成自体干细胞移植并出院。)